2018
DOI: 10.1590/1414-431x20187311
|View full text |Cite
|
Sign up to set email alerts
|

Association between tumor necrosis factor alpha rs1800629 polymorphism and risk of osteoarthritis in a Chinese population

Abstract: Osteoarthritis (OA) is the most common degenerative disease affecting articular cartilage. Some studies indicate that tumor necrosis factor alpha (TNF-α) gene rs1800629 polymorphism was associated with OA risk among Caucasian populations. To examine the role of this candidate gene in Asian populations, we conducted a hospital-based case-control study involving 257 knee OA patients and 305 controls in a Chinese population. Genotyping was performed using a custom-by-design 48-Plex single nucleotide polymorphism … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 23 publications
3
16
0
Order By: Relevance
“…On the other hand, Sobhan et al [35] in a case-control study followed by a meta-analysis, demonstrated that this polymorphism in question may not be associated with susceptibility of OA, as other authors complement, ratifying the lack of relationship between the − 308 SNP TNF and OA [32,36]. In contrast, there are several studies with results agreeing with our data, where the presence of the A allele at position − 308 has a direct relation to the prevalence and severity of knee and hip OA [21,22,24,25,33,37], which is associated with a six-fold increase in transcriptional activity and higher levels of TNF-α protein [38,39]. In this same sense, Chen et al 2018 and Kou et al 2014 in metaanalyzes, with 983 and 257 cases of AO and 1355 and 305 controls, respectively, found an association between the − 308 G / A polymorphism of TNF in relation to the higher risk of OA.…”
Section: Discussionsupporting
confidence: 86%
See 2 more Smart Citations
“…On the other hand, Sobhan et al [35] in a case-control study followed by a meta-analysis, demonstrated that this polymorphism in question may not be associated with susceptibility of OA, as other authors complement, ratifying the lack of relationship between the − 308 SNP TNF and OA [32,36]. In contrast, there are several studies with results agreeing with our data, where the presence of the A allele at position − 308 has a direct relation to the prevalence and severity of knee and hip OA [21,22,24,25,33,37], which is associated with a six-fold increase in transcriptional activity and higher levels of TNF-α protein [38,39]. In this same sense, Chen et al 2018 and Kou et al 2014 in metaanalyzes, with 983 and 257 cases of AO and 1355 and 305 controls, respectively, found an association between the − 308 G / A polymorphism of TNF in relation to the higher risk of OA.…”
Section: Discussionsupporting
confidence: 86%
“…Proinflammatory cytokines, such as TNF, are important mediators of this process by activating the production of metalloproteinases by chondrocytes, and stimulating the production of other proteins and cytokines, resulting in catabolic action and suppression of articular anabolism [16,31]. The polymorphisms of these cytokine genes are studied in understanding the complex etiology and pathophysiology of OA, representing a potential tool for identifying risk for the disease, which can be useful in preventive and clinical management [21,22,24,[27][28][29][30][32][33][34]. In this study we assessmnent the polymorphism − 308 G/A TNF with the presence and severity of OA in the elderly.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on Multalin alignment, there was no polymorphism at the position of -308 TNF-α gene promoter in all sample sequences (active and passive smokers, non-smokers and subject samples). The nitrogen base in the nucleotide found in this position was guanine, although there are variations in polymorphism in the form of adenine (Chen et al, 2018). This does not show that although position -308 had polymorphism in other populations, there was no influence of cigarette smoke which causes nucleotide Figure 1.…”
Section: Polymorphism Detectionmentioning
confidence: 84%
“…GG genotype was more than AA and AG in the Brazilian population (Borges et al, 2018). In the Chinese population, the G allele was more common than the A allele, and the genotypes found in the population more are GG and the least AA genotypes were found (Chen et al, 2018). Different results were shown in the North Indian population, where the A allele was more found (Kumari et al, 2018).…”
Section: Polymorphism Detectionmentioning
confidence: 97%